Coping strategies among low-income families in Sweden - Sven Trygged (Social Work & Society, 2020)
From a global perspective, Sweden is a wealthy country with a high gross domestic product, comparatively low-income inequality as measured by the Gini index, a good reputation for transparency, and low poverty rates. However, many people without an established position on the labour market benefit little from Sweden's various forms of social insurance, since the amount of financial compensation one can receive when ill, unemployed, on parental leave, or retired relates to work requirements and previous income. This is one important reason why migrants from the Global South have low family incomes even in the Swedish welfare state and must rely on means-tested social assistance. This research considers what it means for families to live at a low economic standard, their experiences of contacts with the social services, and how they cope with low incomes. Social service clients were recruited from small and medium-sized towns in Sweden. Adults in eleven families of different origins, all long-term dependent on social assistance, were interviewed. The families' efforts to handle their financial situation were interpreted as coping strategies. These strategies were divided into the subcategories action, adaptation, avoidance, and submission, with adaptation to social service demands being the most common strategy. Some migrant adults also expected to receive support from their own children when they grow older.